Analisis Manajemen Risiko dalam Penanganan Pembiayaan Ijarah Multijasa bagi Anggota Meninggal Dunia di KSPPS BMT Artha Buana Kota Metro - Irawan, Dimas Yuda; Santoso, Haris; Khotamin, Nur Alfi (Revenue Journal: Management and Entrepreneurship, 2025)
This study aims to analyze the risk management implementation system in handling Ijarah Multijasa financing for deceased members at BMT Artha Buana Metro, considering that problematic financing cases due to death are still found based on the results of the pre-survey. The background of the study emphasizes the importance of risk mitigation mechanisms to maintain the stability of Islamic financial institutions, especially in Ijarah Multijasa contracts that are vulnerable to the risk of members' inability to fulfill obligations. The study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation of BMT leaders, AO and CS staff, and member heirs. The results show that BMT Artha Buana Metro implements financing risk management through four main stages, namely identification, measurement, monitoring, and risk control. Identification is carried out by analyzing risk characteristics in multi-service financing, while measurement is carried out by evaluating procedures, assumptions, and data used in assessing the level of risk. Monitoring is carried out through periodic evaluations of financing conditions, while risk control is carried out through policies such as cooperation with insurance or takaful institutions, discussions with heirs, and assessment of financing feasibility based on the 5C principle. The research results show that implementing systematic procedures, such as member data verification, coordination with heirs, prompt administrative resolution, and the use of risk protection programs, can minimize the occurrence of problem financing and maintain institutional stability despite the risk of member death.